Redistricting in the elections to the US House of Representatives and its role in the US political system (Economic and Political Thought, 2016)
The main purpose of this article is to analyse the system of redistrictingregarding the elections to the US House of Representatives and to examinewhat consequences it has for the entire political system. The article is basedon a hypothesis that redistricting does not have a direct impact on electionsresults and on the political system. However, it has an important indirectimpact, strengthening already existing trends, and also a mediating impact,consisting in the transmission of changes from one level of the political systemto another level. The article consists of three parts. The first one isdevoted to historical evolution of the redistricting system, from the creationof the United States till the 1960s. The second part discusses three subsequentphases of the evolution of the contemporary redistricting system. Thethird part investigates how redistricting affects the political system as a whole.The following issues are analysed in this part: direct impact on electionsresults, alleged decline in electoral competition, growing polarization of thepolitical arena and the electorate, and representatives’ attentiveness to theirconstituents’ problems.